Immigrant students: Parents’ and teachers’ experience of learning and teaching - Gunnþórsdóttir, Hermína; Barillé, Stéphanie; Meckl, Markus (Menntavísindasvið Háskóla Íslands, 2017)
There is a constantly growing number of students of foreign origin in Icelandic education. These changes require schools and teachers to respond to the educational needs these students may have. The results of Icelandic research on multicultural education have, in the main, suggested that the Icelandic school system is failing in its efforts to educate children of foreign origin. Current legislation on schools in Iceland strongly emphasises equality, and schools are expected to suit their operation as closely as possible to the situation and needs of the students; thus, in a broad sense, supporting every student’s development, welfare and education. This emphasis is reiterated, at each stage, in the Icelandic National Curriculum Guide for Compulsory Schools (Mennta- og menningarmálaráðuneyti, 2012b) Icelandic education policy is based on the ideology of the inclusive school which focuses on meeting students’ diverse needs, whether those be academic or social; thus the operation of the school attempts to ensure that students are given equal or equivalent educational opportunities. The policy also emphasizes the diversity of the student group, leading to their varied needs. Despite the attempt to recognize diversity within the Icelandic school system, for example in legislation and curricula, the multicultural aspect of the education policy has not received much attention. In academic discourse on the inclusive school and multicultural education, research,both in Iceland and abroad shows that impediments to real change towards multicultural practices are not least to be found in attitudes to students who need additional assistance in their studies and in parents’ and teachers’ expectations towards them. When initiating and developing a multicultural, inclusive school operation, respect for families and their diverse backgrounds has a crucial role. School staff have to be prepared to work with parents of varied origin and to demonstrate an understanding of their circumstances and world view. The objective of this ...